Anisotropic Thermal and Guest‐Induced Responses of an Ultramicroporous Framework with Rigid Linkers. Issue 19 (8th March 2018) - Auckett, Josie E.; Duyker, Samuel G.; Izgorodina, Ekaterina I.; Hawes, Chris S.; Turner, David R.; Batten, Stuart R.; Peterson, Vanessa K.
Abstract: The interdependent effects of temperature and guest uptake on the structure of the ultramicroporous metal–organic framework [Cu3 (cdm)4 ] (cdm=C(CN)2 (CONH2 ) − ) were explored in detail by using in situ neutron scattering and density functional theory calculations. The tetragonal lattice displays an anisotropic thermal response related to a hinged "lattice‐fence" mechanism, unusual for this topology, which is facilitated by pivoting of the rigid cdm anion about the Cu nodes. Calculated pore‐size metrics clearly illustrate the potential for temperature‐mediated adsorption in ultramicroporous frameworks due to thermal fluctuations of the pore diameter near the value of the target guest kinetic diameter, though in [Cu3 (cdm)4 ] this is counteracted by a competing contraction of the pore with increasing temperature as a result of the anisotropic lattice response. Abstract : The metal–organic framework [Cu3 (cdm)4 ] exhibits areal negative thermal expansion over a broad temperature range. In situ neutron scattering and DFT calculations provided considerable insight into the underlying atomistic causes of this phenomenon, the influence of adsorbed guest molecules, and the implications for potential temperature‐mediated adsorption in ultramicroporous frameworks (see figure).